A Literature Review on Risk Management in Mudharabah and Musyarakah Financing Products within the Context of Islamic Banking - Khayat, Aghvar Aziz Nur; Wargo; Niskaromah (CV. Zabags Qu Publish, 2025)
Islamic banks operate based on Sharia principles that prohibit riba, gharar, and maysir, promoting a profit-and-loss sharing (PLS) model through Mudharabah and Musyarakah contracts. These contracts embody ideals of fairness and partnership, positioning the bank as a capital provider (shahibul maal) in Mudharabah, and as an equal partner in Musyarakah. However, despite their theoretical advantages, PLS-based financing faces substantial risks in practice, including moral hazard, information asymmetry, and limited monitoring capacity. This study aims to identify the main risks associated with these contracts, evaluate risk management approaches, and compare mitigation strategies across both financing schemes. Using a Systematic Literature Review (SLR) method, the study collected, filtered, and synthesized scholarly publications from 2013 to 2023 sourced from Google Scholar, SINTA, DOAJ, OJK, and BI databases. The thematic analysis reveals recurring issues in governance, supervision, and policy alignment, while also outlining best practices and technological innovations for mitigating risk. This article contributes to both the theoretical understanding and practical application of risk management in Islamic finance by offering comprehensive insights for academic development, industry practices, and regulatory frameworks aimed at enhancing the sustainability and distinctiveness of Islamic banking through optimized equity-based financing models.